Self-Stigma Among People With Mental Health Problems in Terms of Warmth and Competence - Gärtner, Laura; Asbrock, Frank; Euteneuer, Frank; Rief, Winfried; Salzmann, Stefan (Frontiers in Psychology, 2022)
Introduction: Self-stigma arising from public stigma is a heavy burden for people suffering from mental health problems. Both public stigma and self-stigma encompass the same three elements: stereotype, prejudice, and discrimination. Public stigma has already been successfully explored by the Stereotype Content Model (SCM) and the Behaviors from Intergroup Affect and Stereotypes (BIAS) map. However, this is not the case for self-stigma. Therefore, this is the first study that applies SCM and BIAS map to self-stigma by examining whether the effects of self-stereotypes on self-directed discrimination would be mediated by self-directed prejudices in people with mental health problems. Method: Within a total sample of N = 823 participants, who took part in an online survey, n = 336 people reported mental health problems. Mental health and self-stereotypes (warmth, competence), self-directed prejudice (negative emotions), and self-directed discrimination (active/passive self-harm) were assessed. Results: Structural equation modeling supported the hypothesis that the stereotype dimensions warmth and competence negatively relate to prejudice, while stronger prejudice was associated with more discrimination (active/passive self-harm). Prejudice fully mediated the relationship between stereotypes and discrimination. The indirect effects of warmth and competence on active and passive self-harm were moderated by competence and warmth. Discussion: Implications for further research on self-stigma and the usage of SCM and BIAS map are discussed.